The clinical effects of miR-26a, miR-16, let-7, miR-128a and miR-223 in acromegaly - Bosna, Islam Cagri; Edgunlu, Tuba; Akbaba, Gulhan; Yaylali, Guzin Fidan; Celik, Sevim Karakas; Etem, Ebru Onalan; Cinar, Nese (Springer London Ltd, 2025)
BackgroundMicroRNAs (miRNAs) have been shown to function either as oncogenes or tumor suppressors, depending on the cellular context. This study aimed to explore the potential involvement of specific miRNAs in pituitary tumorigenesis and to assess their association with clinical features in patients diagnosed with acromegaly.MethodsThe study comprised 39 acromegaly patients and 39 healthy controls who were matched for age and gender. Real-time PCR was used to determine the miR-26a, let-7, miR-16, miR-223 and miR-128a levels in peripheral blood. The patients' treatment methods, radiographic characteristics of the adenoma, and demographic characteristics were assessed.ResultsWhile patients with acromegaly and controls had similiar miR-26a, miR-16 and miR-128a levels, acromegalics had non-significantly lower let-7 levels [0.68 (0.45-1.05) vs.1.04 (0.53-1.94); p = 0.053] and significantly higher miR-223 levels [1.90 (0.75-3.23) vs. 0.86 (0.52-1.41); p = 0.021] compared to controls. No significant associations were observed between miRNA expression levels and radiological features of the adenoma, including tumor size, optic chiasm compression, and invasion of the cavernous sinus. Moreover, miR-26a expression is demonstrated to be increased in patients who required medical treatment after surgery (n: 26, 66.6%) [1.22 (0.93-1.73) vs. 0.74 (0.61-1.07); p = 0.004].ConclusionThe decreased expression of the tumor-suppressive let-7 and increased levels of the oncogenic miR-223 suggest a potential role in pituitary tumorigenesis in acromegaly. Although these miRNAs were not linked to tumor characteristics, elevated miR-26a expression may serve as a prognostic marker for long-term treatment needs in acromegaly patients.
Keywords: Acromegaly; MicroRNA; Oncogene; Tumor supressor gene